The friaries of medieval London : from foundation to dissolution - Holder, Nick (Archaeologist and historian) (Studies in the history of medieval religion, 2017)
The friaries of medieval London formed an important part of the city's physical and spiritual landscape between the thirteenth and sixteenth centuries. These urban monasteries housed 300 or more preacher-monks who lived an enclosed religious life and went out into the city to preach. The most important orders were the Dominican Black friars and the Franciscan Grey friars but London also had houses of Augustine, Carmelite and Crossed friars, and, in the thirteenth century, Sack and Pied friars. This book offers an illustrated interdisciplinary study of these religious houses, combining archaeological, documentary, cartographic and architectural evidence to reconstruct the layout and organisation of nine priories. After analysing and describing the great churches and cloisters, and their precincts with burial grounds and gardens, it moves on to examine more general historical themes, including the spiritual life of the friars, their links to living and dead Londoners, and the role of the urban monastery. The closure of these friaries in the 1530s is also discussed, along with a brief revival of one friary in the reign of Mary.